2015
DOI: 10.1089/lrb.2014.0009
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Stomata in the Adult Human Pulmonary Ligament

Abstract: Background: Lymphatic stomata are small lymphatic openings in the serosal membrane that communicate with the serosal cavity. Although these stomata have primarily been studied in experimental mammals, little is known concerning the presence and properties of lymphatic stomata in the adult human pleura. Thus, adult human pleurae were examined for the presence or absence of lymphatic stomata. Methods and Results: A total of 26 pulmonary ligaments (13 left and 13 right) were obtained from 15 adult human autopsy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Pleuro-lymphatic communication is made through stomas [ 14 ]. In human, stomas open at the mesothelial surface and extend into a lymphatic capillary connected to the submesothelial lymphatics [ 15 ]. Inhaled asbestos fibres are deposited in the respiratory airways, reach the lung and are translocated into the pleura.…”
Section: Human Malignant Mesotheliomamentioning
confidence: 99%
“…Pleuro-lymphatic communication is made through stomas [ 14 ]. In human, stomas open at the mesothelial surface and extend into a lymphatic capillary connected to the submesothelial lymphatics [ 15 ]. Inhaled asbestos fibres are deposited in the respiratory airways, reach the lung and are translocated into the pleura.…”
Section: Human Malignant Mesotheliomamentioning
confidence: 99%
“…Clearance of exogenous particles from the pleural space occurs by means of an inherent mechanism that involves the stomata in the parietal pleura. Lymphatic stomata are small lymphatic openings in the serous membrane, communicating with the serous cavity the serous cavity [ 10 ]. It has been shown that airborne PM that reaches the lung alveoli enters the pleural space and crosses the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…12 Characteristically, lymphatics originating from the lower thoracic esophagus share with lymphatics originating from the pulmonary ligament, which has lymphatic stomata and a rich lymphatic network. 12 – 14 These lymphatics connect with LNs of the tracheal bifurcation and with celiac LNs to form lymphatic chains. 15 In addition, lymphatics originating from the thoracic esophagus frequently drain into the thoracic duct directly without intervening LNs.…”
Section: Discussionmentioning
confidence: 99%